The Effect Of Suggested Play Based Counseling Program On The Development Of Sense-motor Perception Among Kindergarten Children (5-6) Years Old - Kadri , Ameur; Abbassi , Zohra (sports creativity, 2025)
The research was conducted with the aim of identifying the effect of a suggested counseling program for playing on developing the perception of movement in kindergarten children (5-6) years old with motor learning difficulties. The research and its problem that crystallized included that there is a weakness in some children in their sense of motor abilities as a result of lack of interest in children People with kinesthetic learning difficulties, which called the researcher to study this important aspect and work to improve and develop it by using the method of playing counseling for this age group. Where the experimental method was used by the method of pre and post testing for their suitability to the nature of the problem. It also included a description of the research sample, which numbered (60) children, for the purpose of revealing the reality of the sensory-motor perception. As for the children of the experiment sample, it reached (40) children and children with poor motor perception. After processing the data using the appropriate statistical means (spss), the results resulted in the effectiveness of using the suggested instructional program by playing in developing the sense-kinesthetic perception for kindergartens at the age of (5-6) years, as we concluded the necessity of pairing counseling within the kindergarten curriculum for this to expose the child to many different experiences.